2007
DOI: 10.3349/ymj.2007.48.6.901
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Syndrome and Vascular Ischemic (Occlusive) Diseases: An Overview

Abstract: Antiphospholipid syndrome (APS) is primarily considered to be an autoimmune pathological condition that is also referred to as "Hughes syndrome". It is characterized by arterial and/or venous thrombosis and pregnancy pathologies in the presence of anticardiolipin antibodies and/or lupus anticoagulant. APS can occur either as a primary disease or secondary to a connective tissue disorder, most frequently systemic lupus erythematosus (SLE). Damage to the nervous system is one of the most prominent clinical const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 181 publications
(210 reference statements)
0
19
0
1
Order By: Relevance
“…As cranial nerve palsy progressed after almost 2 months to alteration of consciousness, at that time CT or MRI was the rational imaging of choice at that time 7. The concomitant presence of central and peripheral venous thrombosis has been reported8 in APS as well as Behcet’s disease 9. However, the absence of other markers of Behcet’s such as recurrent oral ulcers or other skin lesions, makes the diagnosis unlikely in our case.…”
Section: Discussionmentioning
confidence: 78%
“…As cranial nerve palsy progressed after almost 2 months to alteration of consciousness, at that time CT or MRI was the rational imaging of choice at that time 7. The concomitant presence of central and peripheral venous thrombosis has been reported8 in APS as well as Behcet’s disease 9. However, the absence of other markers of Behcet’s such as recurrent oral ulcers or other skin lesions, makes the diagnosis unlikely in our case.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study has revealed the knowledge between false-positive TORCH (toxoplasmosis, other: syphilis, varicella-zoster, Rubella, CMV, and herpes infections) and anti-PL opening new diagnostic opportunities, relevant for practical decisions [ 11 ]. Also, in the spectrum of vascular ischaemic occlusive disease in the APS, ulnar artery thrombosis is a rare association [ 12 ]. However, with the acute episode of thrombosis, we were unable to arrange certain other investigations to rule out any concomitant familial thrombophilic disorder screening even though the family history is not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, clearly established deficiencies of proteins C, S, and antithrombin are relatively uncommon. Antiphospholipid antibody syndrome (Atanassova, 2007) (McGinn et al, 2000). In this way, if a rule is applied, it is possible to further identify those CVST patients who could benefit from more intensive monitoring and/or invasive interventions at most.…”
Section: Ealry and Late Complications -Management And Preventionmentioning
confidence: 99%